Impact of Appointment Waiting Time on Attendance Rates at a Clinical Cancer Genetics Service. Issue 6 (24th May 2018) - Shaw, Tarryn; Metras, Julie; Ting, Zoe Ang Li; Courtney, Eliza; Li, Shao‐Tzu; Ngeow, Joanne
Abstract: The increase in demand for clinical cancer genetics services has impacted the ability to provide services timeously. Given limited resources, this often results in extended appointment waiting times. Over the last 3 years, the Cancer Genetics Service at the National Cancer Centre Singapore has continued to experience a steady increase in demand for its service. Nevertheless, significant no‐show rates have been reported. This study sought to determine whether an association exists between appointment waiting times and attendance rates. Data was gathered for all participants meeting inclusion criteria. Attendance rates and appointment waiting times were calculated. The relationship between mean waiting times for those who did and did not attend their scheduled appointments was evaluated using Welch's t test and linear regression model. The results showed a significant difference in mean appointment waiting times between patients who did and did not attend (32.66 versus 43.50 days respectively; p < 0.0001). Furthermore, patients who waited for longer than 37 days were significantly less likely to attend. No‐show rates increased as the waiting time increased, at a rate of 19.60% per 20 days and 21.40% per 30 days. In conclusion, appointment waiting time is a significant predictor for patient attendance. Strategies to ensure patients receive an appointment within the necessary timeframe at the desired setting are important to ensure that individuals at increased cancer risk attend their appointments in order to manage their cancer risks effectively.